Предмет: Алгебра,
автор: Аноним
Преобразуйте выражения в многочлен:
1) (5b-7) (5b+7)
2) (4y+5b) (5b-4y)
3) (9+xy) (9-xy)
4) 10a^2-(1+3a) (3a-1)
Ответы
Автор ответа:
1
1) (5b - 7)(5b +7) = 25b² - 49
2) (4y + 5b)(5b - 4y) = 25b² - 16y²
3) (9 + xy)(9 - xy) = 81 - x²y²
4) 10a² - (1 + 3a)(3a - 1) = 10a² - (9a² - 1) = 10a² - 9a² + 1 = a² + 1
nnast:
пожалуйста) обращайся!
Автор ответа:
0
Ответ:
Объяснение: мне нужно заполнить эту строку поэтому смотрите на картинку
Приложения:
Похожие вопросы
Предмет: Математика,
автор: maurdi473
Предмет: Литература,
автор: Govor685
Предмет: Физика,
автор: rest919
Предмет: Математика,
автор: kirilldenisov1
Предмет: Алгебра,
автор: agnesaudal